Mucosal immunization with a low-energy electron inactivated respiratory syncytial virus vaccine protects mice without Th2 immune bias - Eberlein, Valentina; Rosencrantz, Sophia; Finkensieper, Julia; Besecke, Joana Kira; Mansuroglu, Yaser; Kamp, Jan-Christopher; Lange, Franziska; Dressman, Jennifer; Schopf, Simone; Hesse, Christina; Thoma, Martin; Fertey, Jasmin; et al. (Frontiers in Immunology, 2024)
The respiratory syncytial virus (RSV) is a leading cause of acute lower respiratory tract infections associated with numerous hospitalizations. Recently, intramuscular (i.m.) vaccines against RSV have been approved for elderly and pregnant women. Noninvasive mucosal vaccination, e.g., by inhalation, offers an alternative against respiratory pathogens like RSV. Effective mucosal vaccines induce local immune responses, potentially resulting in the efficient and fast elimination of respiratory viruses after natural infection. To investigate this immune response to an RSV challenge, low-energy electron inactivated RSV (LEEI-RSV) was formulated with phosphatidylcholine-liposomes (PC-LEEI-RSV) or 1,2-dioleoyl-3-trimethylammonium-propane and 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DD-LEEI-RSV) for vaccination of mice intranasally. As controls, LEEI-RSV and formalin-inactivated-RSV (FI-RSV) were used via i.m. vaccination. The RSV-specific immunogenicity of the different vaccines and their protective efficacy were analyzed. RSV-specific IgA antibodies and a statistically significant reduction in viral load upon challenge were detected in mucosal DD-LEEI-RSV-vaccinated animals. Alhydrogel-adjuvanted LEEI-RSV i.m. showed a Th2-bias with enhanced IgE, eosinophils, and lung histopathology comparable to FI-RSV. These effects were absent when applying the mucosal vaccines highlighting the potential of DD-LEEI-RSV as an RSV vaccine candidate and the improved performance of this mucosal vaccine candidate.